Emergence of plasmid-encoded VIM-2–producing Pseudomonas aeruginosa isolated from clinical samples in Lebanon - T. Nawfal Dagher; C. Al-Bayssari; S.M. Diene; E. Azar; J.-M. Rolain (New Microbes and New Infections, 2019)
The present study aimed to describe the emergence of carbapenem-resistant Pseudomonas aeruginosa isolated from clinical Lebanese patients. The resistance of these isolates is due to the presence of the plasmid-encoded blaVIM-2 gene. We provide its first description in Lebanon, as well as a description of disruption of the oprD gene by mutations. Keywords: Carbapenem resistance, oprDgene, Pseudomonas aeruginosa, VIM-2